Health, healing and the church's mission biblical perspectives and moral priorities - Swartley, Willard M., 1936- (Downers Grove, Ill. : IVP Academic, 2012)
Swartley draws together biblical, historical and moral perspectives to help all Christians, including those in health care professions, respond to our current health care challenges. His conclusions will encourage, enlighten and quite possibly, surprise readers.
Healing -- Seven theses: from scripture to today -- Healing in the Old Testament -- Healing in the New Testament and the church's practice -- Biblical theological analysis of healing -- Church as healing community -- Health care: moral-theological perspectives -- Health and health care in Biblical-theological perspective -- Biblical and theological foundations of health care through mutual aid -- Health care in Christian history and mission -- Disability, God's two hands of love: internal care, external witness -- From present systems to new paradigms -- Health care reform: evaluation and prospects -- From high-tech and triage to shalom and service -- Living toward sustainable health care -- Mennonites, brethren and related groups in mission and medicine -- Center for Healing and Hope.
Includes bibliographical references (p. [242]-257) and indexes.
Description based on print version record.
Keywords: Healing -- Religious aspects -- Christianity; Healing -- Biblical teaching; Health -- Religious aspects -- Christianity; Medical care -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books